2022
DOI: 10.1007/s12325-022-02292-1
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Estimated Glomerular Filtration Rate in Adults with Chronic Hypoparathyroidism Treated with rhPTH(1-84): A Retrospective Cohort Study

Abstract: Introduction Chronic hypoparathyroidism is associated with higher risk of developing chronic kidney disease compared with the general population. This study evaluated changes in estimated glomerular filtration rate (eGFR) over a 5-year period in adult patients with chronic hypoparathyroidism treated with recombinant parathyroid hormone (1-84), rhPTH(1-84), compared with a historical control cohort of patients who did not receive rhPTH(1-84). Methods This retrospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Several retrospective cohort studies of adults with chronic hypoparathyroidism treated with PTH therapy as an adjunctive treatment to conventional therapy had preservation of eGFR over 5 years, in contrast to a decline in eGFR in historical control cohorts [13][14][15]. A retrospective cohort study by Rejnmark et al showed that participants with chronic hypoparathyroidism from randomized, double-blind, placebo-controlled trials and open-label studies treated with recombinant human (rh) PTH (1-84) had a 53% lower risk of developing CKD (HR 0.5, 95% CI 0.3-0.9) and 65% lower risk for sustained eGFR decline C 30% from baseline (HR 0.4, 95% CI 0.1-0.9) compared with a historical control cohort of adults with chronic hypoparathyroidism selected from an electronic medical record database who had a prescription for active vitamin D but no use of rhPTH (1-84) or teriparatide [15].…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective cohort studies of adults with chronic hypoparathyroidism treated with PTH therapy as an adjunctive treatment to conventional therapy had preservation of eGFR over 5 years, in contrast to a decline in eGFR in historical control cohorts [13][14][15]. A retrospective cohort study by Rejnmark et al showed that participants with chronic hypoparathyroidism from randomized, double-blind, placebo-controlled trials and open-label studies treated with recombinant human (rh) PTH (1-84) had a 53% lower risk of developing CKD (HR 0.5, 95% CI 0.3-0.9) and 65% lower risk for sustained eGFR decline C 30% from baseline (HR 0.4, 95% CI 0.1-0.9) compared with a historical control cohort of adults with chronic hypoparathyroidism selected from an electronic medical record database who had a prescription for active vitamin D but no use of rhPTH (1-84) or teriparatide [15].…”
Section: Discussionmentioning
confidence: 99%
“…Teriparatide showed efficacy in reducing the risk of fracture and improving vertebral and femoral neck BMD [ 191 ]. A recent study concluded that treatment with recombinant parathyroid hormone (1–84) in patients with chronic hypoparathyroidism over 5 years was associated with stable GFR compared to another untreated cohort in whom GFR declined by 1.67 mL/min/1.73 m 2 per year [ 192 ]. Abaloparatide, a fragment of parathyroid hormone-related peptide, stimulates bone formation and is approved as osteo-anabolic therapy in postmenopausal women with osteoporosis [ 193 ].…”
Section: Prevention and Treatment Of Adb In Ckdmentioning
confidence: 99%